2016
DOI: 10.1097/md.0000000000003847
|View full text |Cite|
|
Sign up to set email alerts
|

A meta-analysis of renal outcomes in living kidney donors

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…recent meta-analysis reported pooled cumulative incidence of ESRD at 1.1% (110 per 10,000) among studies that followed donors for at least 10 years postdonation. 8 However, this estimate draws on studies with varying follow-up times and of heterogeneous populations of donors from many different countries including South Africa, 9 Sweden, 10 South Korea, 11 Pakistan, 12 Singapore, 13 and Egypt 14 and, as such, may not apply to any specific patient population.…”
Section: Discussionmentioning
confidence: 99%
“…recent meta-analysis reported pooled cumulative incidence of ESRD at 1.1% (110 per 10,000) among studies that followed donors for at least 10 years postdonation. 8 However, this estimate draws on studies with varying follow-up times and of heterogeneous populations of donors from many different countries including South Africa, 9 Sweden, 10 South Korea, 11 Pakistan, 12 Singapore, 13 and Egypt 14 and, as such, may not apply to any specific patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The results of different studies are very heterogeneous, which is partly due to differences in the size and composition of the study groups as well as the length of follow-up [2,3]. Both urinary U-Prot and Alb are significantly increased only during the long-term course (>10 years) after DN [36]. Our study is the first to analyze the course of glomerular and tubular urinary proteins after DN over 1 year.…”
Section: Urinary Proteins and Enzymuriamentioning
confidence: 90%
“…The Chronic Kidney Disease Prognosis Consortium reported that the risk of kidney disease at 15 years after donation is 3.5-5.3 times greater than that in the control population [7]. Li et al [20] reported a pooled rate of 1.1% for ESRD, 5.7% for proteinuria, and 20.9% for microalbuminuria at >10 years following donation. A meta-analysis comprising 52 studies with follow-up for 24 years reported a significant increase in relative risk for ESRD of 8.83 (95%CI 1.02-20.93) [1].…”
Section: Long-term Outcome For Kidney Donorsmentioning
confidence: 99%